DOI: 10.5016/dt000614088
|View full text |Cite
|
Sign up to set email alerts
|

Influência do tempo de exposição à obesidade sobre a expressão gênica e protéica do sistema regulador do trânsito de cálcio miocárdico

Abstract: +2Dedico este trabalho às pessoas mais importantes da minha vida, À toda minha famíliaQue soube compreender todos os momentos em que estive ausente, obrigada pelos constantes incentivos e torcida pelo meu futuro. Vocês são essenciais! Aos meus PaisSignificado de devoção e coragem, com o exemplo deles, aprendi que tudo é possível com força de vontade e pensamento positivo, e, sobretudo, a importância da dignidade e do caráter. Amor eterno! Ao meu marido, André, Pelo privilégio de ter você ao meu lado, sempre ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 154 publications
(156 reference statements)
0
1
2
Order By: Relevance
“…Since the beta-adrenergic via is in charge of phosphorylation in the site of serum-16 of the PLB, we can infer that this system was not sufficiently stimulated to lead to changes in the myocardial PLB phosphorylation or that another system was opposed to such an activation. The behavior of pPLB-ser16 in this study is not in accordance with a previous study conducted in our laboratory 12 , in which decreased PLB was found in its phosphorylated state in serum 16 among obese rats treated with the same diet used in this study. We could not find an explanation for these different results; such a divergence could be related to the adiposity index in obese animals, which was 16% higher in the study conducted by Lima-Leopoldo 12 .…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…Since the beta-adrenergic via is in charge of phosphorylation in the site of serum-16 of the PLB, we can infer that this system was not sufficiently stimulated to lead to changes in the myocardial PLB phosphorylation or that another system was opposed to such an activation. The behavior of pPLB-ser16 in this study is not in accordance with a previous study conducted in our laboratory 12 , in which decreased PLB was found in its phosphorylated state in serum 16 among obese rats treated with the same diet used in this study. We could not find an explanation for these different results; such a divergence could be related to the adiposity index in obese animals, which was 16% higher in the study conducted by Lima-Leopoldo 12 .…”
Section: Discussioncontrasting
confidence: 93%
“…The behavior of pPLB-ser16 in this study is not in accordance with a previous study conducted in our laboratory 12 , in which decreased PLB was found in its phosphorylated state in serum 16 among obese rats treated with the same diet used in this study. We could not find an explanation for these different results; such a divergence could be related to the adiposity index in obese animals, which was 16% higher in the study conducted by Lima-Leopoldo 12 . No studies in literature analyzed the relationship between proteins that interfere in myocardial PLB phosphorylation and dephosphorylation in obese rats submitted to a hyperlipidic diet.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation